The Proof and Measurement of Association between Two Things - Spearman, C. (The American Journal of Psychology, 1987)
Keywords: Ouvrage_Collectif_Numéro1

Plant ecological aspects of flood geomorphology and paleoflood history - Hupp, Cliff R. (Flood Geomorphology, 1988)
A landscape is a mosaic of natural and/or artificial communities and wa-terbodies and may contain several distinct ecosystems. Human life depends on many services delivered by the water-based aquatic and land-based terrestrial ecosystems. A wide variety of aquatic ecosystems exist and alt-hough they represent a low percentage of the Earth’s surface, their roles and functions make them crucial. Aquatic ecosystems especially inland aquatic ecosystems are rich in biodiversity and home to a diverse array of species and habitats, providing numerous economic and societal benefits to humans. Understanding diversity of aquatic ecosystems within landscape is a fundamental goal of both basic and applied ecological research. This study recognizes, defines, classifies, characterizes and compares for the first time the aquatic resources vis-à-vis aquatic ecosystems in the landscape of Adilabad District, Telangana, “Deccan Region”, India, which was selected as the study area.
Keywords: Ouvrage_Collectif_Numéro1